2016
DOI: 10.4062/biomolther.2015.109
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin-Mediated ATF3 Expression Contributes to Apoptosis in Human Colon Cancer

Abstract: Naringenin (NAR) as one of the flavonoids observed in grapefruit has been reported to exhibit an anti-cancer activity. Activating transcription factor 3 (ATF3) is associated with apoptosis in human colon cancer cells. This study was performed to investigate the molecular mechanism by which NAR stimulates ATF3 expression and apoptosis in human colon cancer cells. NAR reduced the cell viability and induced an apoptosis in human colon cancer cells. ATF3 overexpression increased NAR-mediated cleaved PARP, while AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 38 publications
(46 reference statements)
1
24
1
Order By: Relevance
“…In a recent study, p38 was demonstrated to be activated by naringenin and to mediate the upregulation of ATF3 in human colon cancer cells32. However, our results showed that naringenin inhibited p38 activation in LPS-treated macrophages, suggesting that p38 may not be required for ATF3 upregulation in macrophages.…”
Section: Discussioncontrasting
confidence: 80%
“…In a recent study, p38 was demonstrated to be activated by naringenin and to mediate the upregulation of ATF3 in human colon cancer cells32. However, our results showed that naringenin inhibited p38 activation in LPS-treated macrophages, suggesting that p38 may not be required for ATF3 upregulation in macrophages.…”
Section: Discussioncontrasting
confidence: 80%
“…ATF3 promotion of apoptosis, a key process in prevention of growth and invasion, may result from KLF6 induction of ATF3 [144] or through its activation of p53 [145]. We found a significant downregulation of KLF6 in the centre KE (p = 0.02) and interestingly, ATF3 has been shown to mediate apoptosis by anti-cancer therapies [146148]. Also in the microdissected KE, UGT3A2 , a member of the UDP-glycosyltransferase superfamily that plays a role in drug metabolism and which may affect detoxification of therapeutic drugs, was found to be strongly under-expressed [149, 150].…”
Section: Resultsmentioning
confidence: 86%
“…prostate, pancreatic, colon, breast, and gastric cancer (Song et al, 2016;Lim et al, 2017;Wang et al, 2019a) sensitizing chemotherapy CDKN2A, BCL2, CASP3/9, BAX, PTK2, MAPK14 lung and pancreatic cancer (Parashar et al, 2018;Lee et al, 2019) inhibiting metabolism AKT1, GTF2H2, MAP2K1/2, MAPK1, NFKB1, PIK3CA breast cancer (Harmon and Patel, 2004) enhancing immunity GZMB, ID2, IFNG, IRF2, SMAD3/7 lung cancer and melanoma (Lian et al, 2018) Naringin anti-proliferation AKT1, BIRC5, CDKN1A, CTNNB1, EGFR, MAPK1, MIR126, MTOR, NFKB, PIK3CA, VCAM1…”
Section: Discussionmentioning
confidence: 99%